(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
The paper aims to analyze Zainabu Jallo as a psychograph and psychogram dramatist. The dramatist as the custodian of the peoples’ culture and values watches the society and the individual and portrays the ills and follies of the society in his/ her works in order to correct them. This study uses the content analysis and relational analysis approach to examine Jallo’s Onions Make us Cry and Holy Night. Her ability to delve into the internal system of the individual and the society with her literary dexterity is highlighted. It is established that as a psychograph and psychogram dramatist, Zainabu Jallo graphically and descriptively exposes the problems prevalent in not just contemporary Nigeria but the global community: Domestic Violence, Terrorism, Religious Crisis and other frustrating individual experiences